1978
DOI: 10.1080/09291017809359626
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in the physiology of the goldfish,Carassius auratus

Abstract: Liver glycogen, liver lipid, liver triglycerides, plasma glucose, plasma total lipid, plasma cholesterol, plasma corticoids, hypothalamic serotonin and pituitary prolactin levels were assayed at five times over a 24-h period in Carassius auratus maintained under a specific photoperiod regime at various times throughout the year. Diurnal variations were observed in all parameters monitored. Daily variations of liver glycogen, plasma glucose, plasma lipid, plasma corticoids and hypothalamic serotonin were affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The data from the experiment reported here suggests that the apparent post-prandial increase in plasma glucose concentrations in rainbow trout is also synchronized with the light/dark alternation. Similar conclusions can be drawn from the studies of Delahunty et al (1978) with Carassius auratus, Gutierrez et al (1984) with Dicentrarchus labrax fed natural diets, and Laidley and Leatherland (1988) with 0. mykiss.…”
Section: Discussionsupporting
confidence: 81%
“…The data from the experiment reported here suggests that the apparent post-prandial increase in plasma glucose concentrations in rainbow trout is also synchronized with the light/dark alternation. Similar conclusions can be drawn from the studies of Delahunty et al (1978) with Carassius auratus, Gutierrez et al (1984) with Dicentrarchus labrax fed natural diets, and Laidley and Leatherland (1988) with 0. mykiss.…”
Section: Discussionsupporting
confidence: 81%
“…The shift in the time of feeding appeared to have a significant effect on the diel plasma cortisol pattern, particularly during the scotophase. A similar disappearance of the peak of cortisol in the scotophase was reported by Delahunty et al (1978) in goldfish when the feeding pattern was changed from a single feed presented early in the day to a single feed administered at random. In rainbow trout given free access to self-demand feeders, a main peak of plasma cortisol concentration was apparent at the time of the major feeding episode (i.e., dawn) (Boujard and Leatherland 1992c); postprandial increases were not evident in the present study possibly because of the method of feeding that was used.…”
Section: Discussionsupporting
confidence: 52%
“…In previous studies, there was no general agreement as to whether circadian rhythms of hepatic glycogen content are present; the considerable variation among these studies with regard to season, photoperiod and feeding regimes employed render comparisons difficult (Delahunty et al 1978;Singh 1981;Laidley and Leatherland 1988). In previous studies in our laboratory, we reported significant increases in hepatic glycogen content in rainbow trout, but as with the T 3 response, this effect was only found in fish given unrestricted access to a self-demand feeder (Boujard and Leatherland 1992c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kizer et al 1975, Lincoln et al 1978, and also in some teleost fishes (Leatherland & McKeown 1973, Sage & de Vlaming 1973, Leatherland et al 1974, Spieler 1975, Delahunty et al 1978a. Changes in photoperiod have been reported to alter pituitary and serum PRL levels in certain mammals (Reiter 1975, Lincoln et al 1978.…”
mentioning
confidence: 99%